EFEKTIVITAS MEDIA PEMBELAJARAN INTERAKTIF IPA BERBASIS DIGITAL DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS V SD NEGERI MULUR 03 - Hidayat, Fikrun Najih; Febriansyah, Wahyu Candra; Khomala, Afrelia Lintang; Adellestia, Geby (LPPM UM Metro, 2025)
This research aims to determine the effectiveness of using digital-based interactive learning media for science in increasing student interest in learning at SD Negeri Mulur 03. The method used is descriptive qualitative research with the research subjects as many as 24 grade 5 students. Data collection instruments include observation, interviews, documentation, and questionnaires. The results showed that the utilization of digital-based interactive learning media can increase students' enthusiasm and participation in the learning process. Although there are obstacles such as signal limitations and teachers' ability to operate technology, the trial results show that the majority of students give a positive response to the use of digital media. Interesting and interactive learning media is proven to be able to foster interest in learning and encourage active involvement of students. This research recommends improving teachers' competence and digital infrastructure as an effort to optimize technology-based learning in primary schools.Keywords:Â Digital learning media, Interest to learn, Science learning, Elementary school